Technical efficiency, efficiency change, technical progress, and productivity growth among national health systems in African continent - Kirigia, J.; Asbu, E.; Greene, William; Emrouznejad, A. (University of Nairobi Press, 2013)
© University of Nairobi Press, 2013. All rights reserved. In May 2006, the Ministers of Health of all the countries in the African continent, at a special session of the African Union, undertook to institutionalise efficiency monitoring within their respective national health information management systems. The specific objectives of this study were to assess the technical efficiency of National Health Systems (NHSs) of African countries for producing male and female life expectancies and to assess changes in health productivity over time with a view to analysing changes in efficiency and changes in technology. The analysis was based on a five year panel data (1999 2003) from all the 53 countries of continental Africa. Data envelopment analysis (DEA) - a non parametric linear programming approach - was employed to assess technical efficiency. The Malmquist total factor productivity (MTFP) was used to analyse efficiency and productivity change over time among the national health systems of the 53 countries. The data consisted of two outputs (male and female life expectancies) and two inputs (per capital total health expenditure and adult literacy). The DEA revealed that 49 (92.5%) countries' national health systems were run inefficiently in 1999 and 2000 while 50 (94.3%), 48 (90.6%), and 47 (88.7%) were operated inefficiently in 2001, 2002, and 2003 respectively. Fifty two countries did not experience any change in scale efficiency, while thirty (56.6%) countries' national health systems had a pure efficiency change (PEFFCH) index of less than one signifying that those countries' NHSs pure efficiency contributed negatively to productivity change. All the 53 countries' national health systems registered improvements in total factor productivity attributable mainly to technical progress. Over half of the countries' national health systems had a pure efficiency index of less than one signifying that those countries' NHSs pure efficiency contributed negatively to productivity change. African countries may need to critically evaluate the utility of institutionalising of the Malmquist TFP type of analyses to monitor the changes in health systems economic efficiency and productivity over time.